Development of a recombinant, chimeric tetravalent dengue vaccine candidate. Issue 50 (10th December 2015) - Osorio, Jorge E.; Partidos, Charalambos D.; Wallace, Derek; Stinchcomb, Dan T.
Abstract: Dengue is a significant threat to public health worldwide. Currently, there are no licensed vaccines available for dengue. Takeda Vaccines Inc. is developing a live, attenuated tetravalent dengue vaccine candidate (TDV) that consists of an attenuated DENV-2 strain (TDV-2) and three chimeric viruses containing the prM and E protein genes of DENV-1, -3 and -4 expressed in the context of the attenuated TDV-2 genome backbone (TDV-1, TDV-3, and TDV-4, respectively). TDV has been shown to be immunogenic and efficacious in nonclinical animal models. In interferon-receptor deficient mice, the vaccine induces humoral neutralizing antibody responses and cellular immune responses that are sufficient to protect from lethal challenge with DENV-1, DENV-2 or DENV-4. In non-human primates, administration of TDV induces innate immune responses as well as long lasting antibody and cellular immunity. In Phase 1 clinical trials, the safety and immunogenicity of two different formulations were assessed after intradermal or subcutaneous administration to healthy, flavivirus-naïve adults. TDV administration was generally well-tolerated independent of dose and route. The vaccine induced neutralizing antibody responses to all four DENV serotypes: after a single administration of the higher formulation, 24–67%% of the subjects seroconverted to all four DENV and >80% seroconverted to three or more viruses. In addition, TDV induced CD8 + T cell responses to the non-structural NS1, NS3 and NS5 proteins of DENV. TDV has been also shown to be generally well tolerated and immunogenic in a Phase 2 clinical trial in dengue endemic countries in adults and children as young as 18 months. Additional clinical studies are ongoing in preparation for a Phase 3 safety and efficacy study.